Chipped porcelain-fused-to-metal restoration repaired by the novel self-glazed zirconia veneering with a digital workflow. (17th August 2020) - Ren, Wen; Yang, Li; Du, Faliang; Huang, Jiangyong; Huang, Zhu; Liang, Tingting; Li, Fuyao; Li, Yuanjing; Jiang, Qianzhou; Yang, Xuechao; Guo, Lvhua; Wu, Jingwen
ABSTRACT: In the clinical application of traditional porcelain-fused-to-metal crowns and bridges, porcelain chipping has appeared as the major problems encountered by dentists. Once fracture occurs, neither aesthetics nor chewing efficiency remains. It is difficult to meet clinical needs with current repairing options. Self-glazed zirconia has been developed recently and is widely used in crowns, bridges, and veneering owing to its high strength, low wear on opposite teeth, and aesthetic appeal. In this study, we explore the application prospect of the chipped porcelain-fused-to-metal restoration repaired by the novel self-glazed zirconia veneering with a digital workflow. The results demonstrated that self-glazed zirconia can meet both the aesthetical and functional requirements of anterior and molar teeth in a timely and efficient manner.